Phytochemical Screening and Antioxidant Activities of Rytigynia nigerica (S. Moore) Robyns Roots Extracts - Odeja, Oluwakayode Olubunmi; Ibok, Michael Gabriel; Okpala, Ejike O.; Afolabi-Owolabi, Oluwafunke Toyin; Oluwafemi, Kola Augustus; Adja, Emmanuel; Nosiru, Idris Abayomi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Rytigynia nigerica (Rubiaceae), a medicinal herb native to West Africa, is known for its antimalarial and anticancer properties and is traditionally used to treat various ailments. However, the biological activities of R. nigerica have not yet been fully studied. However, this study was designed to extract, analyse, and evaluate the antioxidant potential and phytochemical screening in the root extracts of R. nigerica. The roots were obtained from the Forestry Research Institute of Nigeria (FRIN), Ibadan and authenticated. The air-dried and pulverised root samples were extracted with methanol using the Maceration method and then partitioned into n-hexane and ethyl acetate using the liquid-liquid extraction method. The phytochemical screening was evaluated using the standard method, while antioxidant activity was investigated viz 2, 2-diphenyl-1-picrylhydrazyl radical (DPPH) assays. The phytochemical screening analysis revealed the presence of saponins, cardiac glycosides, tannins, phenols, reducing sugars, alkaloids and resins in the root extract. The antioxidant activity of the extracts was significant when compared to reference standards. The percentage inhibition of the antioxidant extracts and reference standard are as follows: n-hexane extract (58.50 -45.08%), ethyl acetate extract (90.62-67.82%), Methanol extract (70.81-52.97%), Vitamin C (95.66-91.63%) and butyl hydroxyanisole (94.76-90.96%). The antioxidant inhibition of the free radical was concentration-dependent. The results obtained in this study indicate that R. nigerica root extracts exhibit antioxidant properties, suggesting potential pharmaceutical applications.